Skagway, Alaska, October 1897. - La Roche, Frank (1897)
Caption on image: ""Skaguay, October 1897"" ""Skaguay, October, 1897. The town of Skaguay at present has a population of nearly 3,000 and there is every reason to anticipate a considerable increase at an early date. Skaguay is of as much relative importance to the trail named after it as is its northern neighbor, Dyea, is to the Dyea Trail. A wagon road is being made from the town to Summit Lake, about twenty miles ahead, the work having been undertaken by a local transportation company. The road is to be fourteen feet wide, covered with gravel and if possible, to be kept open the year round. Skaguay has three docks which are shown in the photograph, and besides several hundred frame and log houses it has six hotels, fifteen restaurants and thirteen general merchandise stores."" (Frank La Roche, En Route to the Klondike, 1898) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number